2019
DOI: 10.1139/apnm-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral chemoreceptor deactivation attenuates the sympathetic response to glucose ingestion

Abstract: Acute increases in blood glucose are associated with heightened muscle sympathetic nerve activity (MSNA). Animal studies have implicated a role for peripheral chemoreceptors in this response, but this has not been examined in humans. Heart rate, cardiac output (CO), mean arterial pressure (MAP), total peripheral conductance (TPC), and blood glucose (BG) concentrations were collected in 11 participants. MSNA was recorded in a subset of 5 participants via microneurography. Participants came to the lab on two sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Despite present findings, there is a growing body of literature to support a role for the CB chemoreceptors in glucose regulation (10,11,20,26). The majority of studies examining a role for the carotid chemoreceptors in glucose regulation in humans were carried out in the setting of high insulin (e.g., hyperinsulinemic clamp, mixed meal) (45,55,57). Because of combined changes in both systemic glucose and insulin, it is difficult to fully elucidate the mechanisms and/or factors that may be driving previous findings.…”
Section: Perspectives and Significancecontrasting
confidence: 57%
See 1 more Smart Citation
“…Despite present findings, there is a growing body of literature to support a role for the CB chemoreceptors in glucose regulation (10,11,20,26). The majority of studies examining a role for the carotid chemoreceptors in glucose regulation in humans were carried out in the setting of high insulin (e.g., hyperinsulinemic clamp, mixed meal) (45,55,57). Because of combined changes in both systemic glucose and insulin, it is difficult to fully elucidate the mechanisms and/or factors that may be driving previous findings.…”
Section: Perspectives and Significancecontrasting
confidence: 57%
“…Present data suggest that the CB chemoreceptors are not necessary for the sympathoexcitatory response to steady-state insulin infusion in healthy humans in the hyperinsulinemic range tested (~50 mg/dL). However, Smorschok et al recently observed an increase in MSNA following glucose ingestion that was attenuated when individuals breathed 100% O 2 acutely (45). Our data would suggest that any role for the CB chemoreceptors in the rise in MSNA is unrelated to their ability to sense and/or respond to increases in plasma insulin commonly seen following glucose ingestion.…”
Section: Perspectives and Significancementioning
confidence: 42%
“…Chemoreflex sensitization is a contributing factor to neurovascular dysfunction in many clinical disorders, including heart and renal failure, hypertension and sleep apnea (Kara, Narkiewicz, & Somers, 2003;Prabhakar & Peng, 1985). Evidence have suggested that both glucose (Koyama et al, 2000;Smorschok et al, 2018) and insulin (Limberg, Curry, Prabhakar, & Joyner, 2014) levels play a role in the sensitivity of the chemoreflex during acute and chronic stimulation. For instance, Smorschok et al (2018) found that in non-pregnant populations, the SNA response to glucose ingestion (75 g glucose drink) is blunted (decrease of approximately 35%) with hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence have suggested that both glucose (Koyama et al, 2000;Smorschok et al, 2018) and insulin (Limberg, Curry, Prabhakar, & Joyner, 2014) levels play a role in the sensitivity of the chemoreflex during acute and chronic stimulation. For instance, Smorschok et al (2018) found that in non-pregnant populations, the SNA response to glucose ingestion (75 g glucose drink) is blunted (decrease of approximately 35%) with hyperoxia. It is important to acknowledge that postprandial glucose/insulin could have remained higher in women with GDM, and therefore, hyperoxia would be more effective in blunting SNA in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation